2015
DOI: 10.1186/s12889-015-2360-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting attendance to cervical cancer screening among women in the Paracentral Region of El Salvador: a nested study within the CAPE HPV screening program

Abstract: BackgroundCervical cancer is the third most commonly occurring cancer among women and the fourth leading cause of cancer-related deaths in women worldwide, with more than 85 % of these cases occurring in developing countries. These global disparities reflect the differences in cervical cancer screening rates between high-income and medium- and low-income countries. At 19 %, El Salvador has the lowest reported screening coverage of all Latin American countries. The purpose of this study is to identify factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 17 publications
1
26
1
3
Order By: Relevance
“…The study selection flow diagram is presented in Figure 2. We retained 22 primary studies: 5 of qualitative methodology [29][30][31][32][33], 15 of quantitative methodology [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 2 in which both methodologies were used [49,50]. Seventeen studies originate in high income countries (8-USA, 2-Canada, 5-Europe and 2 in Australia) and five in low and middle income countries (1-Mexico, 1-El Salvador, 1-China, 1-India and 1 in Nigeria).…”
Section: Summary Of Included Studies and Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…The study selection flow diagram is presented in Figure 2. We retained 22 primary studies: 5 of qualitative methodology [29][30][31][32][33], 15 of quantitative methodology [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 2 in which both methodologies were used [49,50]. Seventeen studies originate in high income countries (8-USA, 2-Canada, 5-Europe and 2 in Australia) and five in low and middle income countries (1-Mexico, 1-El Salvador, 1-China, 1-India and 1 in Nigeria).…”
Section: Summary Of Included Studies and Study Qualitymentioning
confidence: 99%
“…Subjective norms comprise healthcare provider (HCP) recommendation [29,36,38,39,44,46,49,50], screening guidelines [29,40,44,50], and the opinions of spouse and friends [29,40,42,44,50].…”
Section: Attitudes Beliefs and Subjective Normsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, El Salvador introduced HPV DNA testing into the public sector through the Cervical Cancer Prevention (CAPE) initiative . However, one study showed that 25%–30% of targeted women in rural areas did not attend scheduled provider‐based screenings. Self‐sampling could increase screening coverage: Rosenbaum et al .…”
Section: Introductionmentioning
confidence: 99%
“…can reduce the number of women remaining outside the programs [19,20] . The option of using liquid-based cytology also helps these initiatives to reduce disparities and facilitate the integration of many women into screening programs since certain HPV tests can be made inside the mobile units, either collected by a physician or nurse, or self-collected, which is a tremendous advance for zones without medical assistance [21] .…”
Section: Discussionmentioning
confidence: 99%